Functional characterization and comparison of intercellular communication in stem cell-derived cardiomyocytes - Marcu, Irene; Illaste, Ardo; Heuking, Pernilla; Jaconi, Marisa E.; Ullrich, Nina D. (Stem cells, 2015)
One novel treatment strategy for the diseased heart focuses on the use of pluripotent stem cell-derived cardiomyocytes (SC-CMs) to overcome the heart's innate deficiency for self-repair. However, targeted application of SC-CMs requires in-depth characterization of their true cardiogenic potential in terms of excitability and intercellular coupling at cellular level and in multicellular preparations. In this study, we elucidated the electrical characteristics of single SC-CMs and intercellular coupling quality of cell pairs, and concomitantly compared them with well-characterized murine native neonatal and immortalized HL-1 cardiomyocytes. Firstly, we investigated the electrical properties and Ca2+ signaling mechanisms specific to cardiac contraction in single SC-CMs. Despite heterogeneity of the new cardiac cell population, their electrophysiological activity and Ca2+ handling were similar to native cells. Secondly, we investigated the capability of paired SC-CMs to form an adequate subunit of a functional syncytium and analyzed gap junctions and signal transmission by dye transfer in cell pairs. We discovered significantly diminished coupling in SC-CMs compared with native cells, which could not be enhanced by a coculture approach combining SC-CMs and primary CMs. Moreover, quantitative and structural analysis of gap junctions presented significantly reduced connexin expression levels compared with native CMs. Strong dependence of intercellular coupling on gap junction density was further confirmed by computational simulations. These novel findings demonstrate that despite the cardiogenic electrophysiological profile, SC-CMs present significant limitations in intercellular communication. Inadequate coupling may severely impair functional integration and signal transmission, which needs to be carefully considered for the prospective use of SC-CMs in cardiac repair. Stem Cells 2015;33:2208-2218